Consequences of Hypoacidity Induced by Proton Pump Inhibitors - a Practical Approach - Rychlíčková, J (Klinicka onkologie, 2018)
BACKGROUND: Proton pump inhibitors (PPIs) are often a part of drug regimens for many patients, including cancer patients. These drugs are very effective suppressors of gastric acid secretion; a significant increase in the gastric pH is seen with chronic use. This affects absorption of drugs, vitamins, and minerals. PURPOSE: PPIs are associated with many adverse drug reactions; nevertheless, these adverse effects are often neglected in clinical practice. The main aim of this article is to emphasize some of the adverse effects and theoretical mechanisms underlying these adverse reactions, the expected length of therapy before their clinical manifestation, and potential ways of dealing with these adverse reactions. We will focus on hypergastrinemia and rebound hyper-acidity, which occur in patients on long-term therapy with high dose PPIs. Next, we will focus on osteoporosis and hypomagnesemia, adverse effects for which the assumed mechanism is decreased absorption of particular ions from the gastrointestinal tract. Furthermore, clinically significant pharmacokinetic drug interactions at the level of absorption will be analyzed. Tyrosine kinase inhibitors (TKIs) are drugs with limited solubility; this solubility is pH-dependent. Some recommendations seek to ensure optimal absorption with minimal inter-day variability. Tables sum-marizing the optimal relationship between food and TKIs, and (sometimes) the optimal regimen of concomitant PPIs, are included. Key words: proton pump inhibitors - drug-related side effects and adverse reactions- drug interactions - tyrosine kinase inhibitors - hypochlorhydria The author declares she has no potential conflicts of interest concerning drugs, products, or services used in the study. The Editorial Board declares that the manuscript met the ICMJE recommendation for biomedical papers. Submitted: 24. 8. 2018 Accepted: 17. 10. 2018.
Keywords: Proton Pump Inhibitors; nádory; Drug Interactions; products; Protein Kinase Inhibitors; or services used in the study. The Editorial Board declares that the manuscript met the ICMJE recommendation for biomedical papers. Submitted: 24. 8. 2018 Accepted: 17. 10. 2018; Gastric Acid; Humans; koncentrace vodíkových iontů; lidé; žaludeční kyselina; inhibitory proteinkinas; inhibitory protonové pumpy; lékové interakce; Neoplasms; Hydrogen-Ion Concentration; proton pump inhibitors - drug-related side effects and adverse reactions- drug interactions - tyrosine kinase inhibitors - hypochlorhydria The author declares she has no potential conflicts of interest concerning drugs